Entwicklung von prozessorientierten Informationssystemen für die industrielle Dienstleistungsbeschaffung - Herfurth, Maik (KIT Scientific Publishing, 2014)
The domain of industrial service procurement lacks in adequate domain-specific solutions for the precise modeling, qualitative and quantitative analysis and implementation of electronic business processes in process-aware information systems. In this work new solutions based on methods, models and e-business solutions are worked out in order to improve the development and configuration of process-aware information systems.